GATOOL - Genome Assembly Tool: uma ferramenta web para montagem de genomas bacterianos - Oliveira, Matheus Brito de (2017)
The assembly of bacterial genomes consists of a process of reordering fragments so that the original genome can be represented. However, to maximize the results of genome assembly, some steps are required, for instance, read quality analysis and preprocessing, repetition identification and quality check. The process of assembly of genomes is a complex step that involves the type of sequencing that was used, there are several types of sequencers which imply different characteristics for each one for example: fragments size, throughput, among others. Analyzing these characteristics requires the use of several computational tools, to assist in all the processes mentioned above, and since the range of software available is quite broad and distinct, it is necessary for the user to learn to work with this computational diversity, dominating often knowledge that is not of the biological area, implying in less time for a deepening in biological questions. Based on this context, we developed a pipeline to perform an automated fragment analysis, read preprocessing, genome assembly and orientation of contigs, having as the assembly the main objective of the pipeline and that it will be managed by a Web application called GATOOL (Genome Assembly Tool). Aiming to evaluate the performance of the application, tests were carried out with two samples of prokaryotic organisms, which are: Bacillus amyloliquefaciens and Serratia marcescens. Also perform a test with seven SRA samples. Both organisms are sequenced on the Ion PGMTM platform. The tools used to perform the assembly were SPAdes and Velvet, both assemblers use de Bruijn graph algorithm as a paradigm for the assembly of the genome, after this stage the resulting set of contigs was ordered through the CONTIGuator, which is a reference ordering. We observed that the interface GATOOL allowed a quick and easy execution of several steps and processes in the field of genome assembly, including the assembly of two prokaryotic species in an automated way, thus facilitating the use and accomplishment of such processes by any user.